Impact of advanced liver fibrosis on atrial fibrillation recurrence after ablation in non-alcoholic fatty liver disease patients - Wang, Zhe; Wang, Yijia; Luo, Fangyuan; Zhai, Yafei; Li, Jiaju; Chen, Yinong; Li, Qing; Zhu, Longyang; Jiao, Siqi; Liu, Peng; Zhou, Yifeng; Chen, Yingwei; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aim Advanced liver fibrosis is independently associated with new onset of atrial fibrillation (AF). Noninvasive liver fibrosis scores are considered an effective strategy for assessing liver fibrosis. This study aimed to investigate the association between advanced liver fibrosis and AF recurrence after ablation in patients with nonalcoholic fatty liver disease (NAFLD). Methods A total of 345 AF patients with NAFLD who underwent de novo ablation between 2019 and 2020 at 2 large hospitals in China were included in this study. AF recurrence was defined as the occurrence of atrial arrhythmia for more than 30 seconds by electrocardiogram or 24-hour Holter monitoring after the first three months of ablation. Predictive values of nonalcoholic fatty liver disease fibrosis (NFS) and Fibrosis-4 (FIB-4) scores for AF burden and recurrence after ablation were assessed. Results At the 1-year follow-up after ablation, 38.8% of patients showed recurrence. Patients with recurrence who had higher FIB-4 and NFS scores were more likely to have persistent AF and duration of AF ≥3 years. In Kaplan–Meier analysis, patients with intermediate and high NFS and FIB-4 risk categories had a higher risk of AF recurrence. Compared to patients with the lowest risk, intermediate and high NFS and Fib-4 scores were independently associated with AF recurrence in multivariate Cox regression analysis (high risk: NFS, HR: 3.11, 95%CI: 1.68~5.76, p < 0.001; FiB-4, HR: 3.91, 95%CI: 2.19~6.98, p < 0.001. intermediate risk: NFS, HR: 1.85, 95%CI: 1.10~3.10, p = 0.020; FiB-4, HR: 2.08, 95% CI: 1.27~3.41, p = 0.003). Conclusion NFS and FIB-4 scores for advanced liver fibrosis are associated with AF burden. Advanced liver fibrosis is independently associated with AF recurrence following ablation. Advanced liver fibrosis might be meaningful in risk classification for patients after AF ablation.